Public support for police use of SWAT: examining the relevance of legitimacy. Issue 1 (1st January 2019) - Moule, Richard K.; Parry, Megan M.; Fox, Bryanna
ABSTRACT: For five decades, law enforcement agencies have developed specialized units, such as Special Weapons and Tactics (SWAT) teams, for dealing with dangerous situations. In recent years, the uses of SWAT have expanded to a number of circumstances. The President's Task Force on 21st Century Policing noted that improper use of SWAT may damage the publics' relationship with police. The current study examines public support for police use of SWAT across a number of different situations, using a national sample of 702 American adults. Descriptive statistics indicate widespread support for the use of SWAT in circumstances associated with hostage situations and terror events, with lower levels of support for circumstances involving the serving of drug warrants, large-scale public events, and peaceful protests, among others. Results from a series of logistic regressions indicate that legitimacy has inconsistent effects on public support for police use of SWAT across circumstances. Implications for theory and policy are discussed.